If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + 10) = 0 Reorder the terms: 6(10 + 4x) = 0 (10 * 6 + 4x * 6) = 0 (60 + 24x) = 0 Solving 60 + 24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 24x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 24x = 0 + -60 24x = 0 + -60 Combine like terms: 0 + -60 = -60 24x = -60 Divide each side by '24'. x = -2.5 Simplifying x = -2.5
| -2(6x-8)=-56 | | (-6+7p)=164 | | 1/6*k=-11 | | -4=4v+8 | | Log(5)*125=3x+2 | | 6/4÷-4 | | y=-16x^2+32x+100 | | x^2=12x-12 | | 3(4w+9)=8 | | 60+10X-K=0 | | 0.09xX=100.56 | | -11x+134=519 | | 4x^2=4x^2+4x-15 | | 2=3x+38 | | 39.95+.12x=19.95+.28x | | (5x+30)=125 | | 32+1.8c=-80 | | 12x+15=36-8x | | 12+4(x-2)= | | x-15x=-120 | | 6m-11=12-2m | | A+B+C=2 | | 3x-12/3x^2-12 | | 4X(x+1)=4x^2+4x-15 | | -4x+5(2x-40)=-140 | | N/25=25 | | Z^6-(1+2i)z^3-7+i=0 | | -86+23x=114+27x | | 5(3+m)-4= | | 4x^2-16x+3y^2-24y+100=0 | | f(-x)=x^2+3x+7 | | 2x-18=4x-29+13 |